N-Terminal Pro-B-Type Natriuretic Peptide as a Biomarker of Bronchopulmonary Dysplasia or Death in Preterm Infants: A Retrospective Cohort Analysis - Zhou, Lin; Xiang, Xiaowen; Wang, Li; Chen, Xuting; Zhu, Jianxing; Xia, Hongping (Frontiers in Pediatrics, 2019)
Objectives To investigate the association between serum N-terminal pro-B-type natriuretic peptide (NT-proBNP) level on the first day of life and a composite outcome of bronchopulmonary dysplasia (BPD) or death in a cohort of infants born before 32 weeks of gestation. Methods We retrospectively identified infants born before 32 weeks of gestation who had serum NT-proBNP levels measured when they were admitted to the Neonatal Intensive Care Unit shortly after birth. The outcome of BPD or death was assessed at 36 weeks of postmenstrual age. The association of serum NT-proBNP levels with BPD or death was evaluated. Receiver operator characteristic (ROC) curve analysis was used to evaluate the predictive performance of serum NT-proBNP levels. Results A hundred and forty-seven preterm infants had serum NT-proBNP levels measured on the first day of life. Serum NT-proBNP level was significantly higher in preterm infants who developed moderate/severe BPD or died (3855 (2567 to 6369) vs. 1259 (950 to 2035) in control infants, P < 0.001). On binary regression analysis, a high natural logarithm of serum NT-proBNP levels was associated with increased risk of moderate/severe BPD or death adjusted for gestational age, birth weight, birth weight z-score, and Apgar scores at 1 and 5 minutes (odds ratio [OR] = 5.195, 95% confidence interval [CI] 2.667-10.117, P < 0.001). ROC analysis identified a NT-proBNP level of 2002.5 pg/mL to have 87.5% sensitivity and 74.7% specificity for predicting moderate/severe BPD or death. The area under the curve (AUC) was 0.853 (95% CI 0.792-0.914). Conclusion Serum NT-proBNP level measured on the first day of life is a promising biomarker for predicting the development of moderate/severe BPD or death in preterm infants. Our findings warrant a larger prospective study to incorporate measurement of NT-proBNP in prognosticating outcomes in very preterm infants.